Effect of Exogenous Gibberellin, Paclobutrazol, Abscisic Acid, and Ethrel Application on Bulblet Development in Lycoris radiata - Xu, Junxu; Li, Qingzhu; Li, Ye; Yang, Liuyan; Zhang, Yongchun; Cai, Youming (Frontiers in Plant Science, 2021)
Lycoris species have great ornamental and medicinal values; however, their low regeneration efficiency significantly restricts their commercial production. Exogenous hormone application is an effective way to promote bulblet development, but their effect on L. radiata has not been verified to date. In the present study, we examined the effect of different exogenous hormones on bulblet development in L. radiata, and found that gibberellic acid (GA) significantly inhibited, whereas paclobutrazol (PBZ), abscisic acid (ABA), and ethrel promoted bulblet development, especially PBZ, a GA biosynthesis inhibitor. Furthermore, GA reduced endogenous cytokinin (CK) content as well as the activities of carbohydrate metabolism enzymes, including sucrose synthase (SUS) and glucose-1-phosphate adenylyltransferase (AGPase), by downregulating the expression levels of LrSUS1, LrSUS2, and genes encoding AGPase large and small subunits. This resulted in the decrease in carbohydrate accumulation in the bulblets, thus hindering their development. PBZ had the opposite effect to GA on carbohydrate metabolism; it decreased endogenous GA15 and GA24, thereby promoting bulblet development. ABA promoted endogenous auxin content and the activities of starch synthesis enzymes, especially soluble starch synthase (SSS) and granule-bound starch synthase (GBSS), through the up-regulation of the expression levels of LrSS1, LrSS2, and LrGBSS1 genes, which could also result in the accumulation of carbohydrates in the bulblets and promote their development. In addition, ethrel application partly promoted bulblet development by promoting endogenous CK content. Although the accumulation of carbohydrates and the activity of starch enzymes were increased by ethrel treatment, we hypothesized that the effect of ethrel on regulating carbohydrate metabolism may be indirect. Our results could provide a basis for improving the propagation efficiency of L. radiata for production, as well as propose some directions for future research.